2019
DOI: 10.1186/s12544-018-0343-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a momentum based impact model in frontal car collisions for the prospective assessment of ADAS

Abstract: Motivation: The advent of active safety systems calls for the development of appropriate testing methods that are able to assess their capabilities to avoid accidents or lower impact speeds and thus, to mitigate the injury severity. Up to now the assessment is mostly based on the decrease of the collision speed due to CMS (collision mitigation systems). In order to assess the effects on injury severity developing methods, that are able to predict collision parameters correlating with the risk of getting injure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The procedure uses programs used in the reconstruction of road accidents and requires solving collision modelling problems. The crash modelling has been covered in other papers [19,20,21].…”
Section: Verification Of Collision By the Sdc Methodsmentioning
confidence: 99%
“…The procedure uses programs used in the reconstruction of road accidents and requires solving collision modelling problems. The crash modelling has been covered in other papers [19,20,21].…”
Section: Verification Of Collision By the Sdc Methodsmentioning
confidence: 99%
“…It mostly applies to the impacts of vehicles the geometric compatibility of which is inconsistent, which has also been discussed in other studies [13]. Solving problems of collision modeling is also discussed in Reference [14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…Gulino et al [20] defined a Crash Momentum Index (CMI) and demonstrated its effectiveness in assessing the performance of ADAS in critical road scenarios. Smit et al [21] pointed out the interest of developing appropriate testing methods to assess the safety capabilities of ADAS (avoiding accidents or mitigating the injury severity). They proposed an impact model which aims to predict collision parameters (here delta-v).…”
Section: Related Workmentioning
confidence: 99%